Gradient patterns in the Tatra Mountain lakes revisited with invertebrate DNA metabarcoding - Ondrej Vargovčík; Kornélia Tuhrinová; Pavel Beracko; Jiří Kopáček; Zuzana Čiamporová-Zaťovičová; Patrik Macko; Michaela Šamulková; Fedor Čiampor (Metabarcoding and Metagenomics)
Monitoring changes in freshwater fauna requires timely, efficient, and comprehensive data collection, needs that are increasingly met by molecular methods. This is especially important in remote regions along environmental gradients, such as the Tatra Mountain lakes in Slovakia. In this study, DNA metabarcoding was applied to littoral benthic invertebrates collected from lakes in three valleys, spanning a gradient from the subalpine to alpine zones. Ordination analyses grouped the lakes based on community composition, and these groups were evaluated in relation to altitude, physico-chemical properties, indicator species, and previous data. To assess their additional value, surface sediment samples from the littoral zone were also analyzed using metabarcoding. The results revealed two distinct lake groups, primarily differentiated by altitude, alkalinity, and other correlated environmental parameters. The placement of specific lakes within these groups corresponded with known patterns of recovery from acidification, catchment characteristics, and potentially climate change or lake connectivity. Metabarcoding-based indicator species analysis successfully identified even taxa that had been previously overlooked or misidentified in morphology-based studies. While sediment metabarcoding provided limited supplementary information, its ordination patterns aligned with those from invertebrate analyses. Overall, our study of an alpine lake system supports broader trends: species richness declines with increasing elevation; community composition reflects environmental gradients; and DNA metabarcoding offers high taxonomic resolution and valuable insights into freshwater invertebrate biodiversity.